If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4 = y + 1 Reorder the terms: 4 + 2x = y + 1 Reorder the terms: 4 + 2x = 1 + y Solving 4 + 2x = 1 + y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2x = 1 + -4 + y Combine like terms: 4 + -4 = 0 0 + 2x = 1 + -4 + y 2x = 1 + -4 + y Combine like terms: 1 + -4 = -3 2x = -3 + y Divide each side by '2'. x = -1.5 + 0.5y Simplifying x = -1.5 + 0.5y
| [-3x+15]=6 | | 282x3/x=47 | | 2x+11=23-4x | | 5/8*w=6 | | 1.3+p=7.9 | | 3.06=n-6 | | -3X-1=10X-78 | | -4+12=24 | | 4h-7=33 | | 2y=3-4x | | 3z-4z=28 | | 6h-7=33 | | -8x^2+48t=0 | | 143+6x+17=180 | | 2x-5+3x+1=56 | | y^2-15=-2y | | 6n-12=3(2n-5) | | 5x+9-x=13 | | a+19=30 | | t=5s+4.15 | | 50=18-8a | | 5(x-8)-40x+13=-27 | | Z-w=6 | | 311=y-181 | | 2y+10=2(y+5) | | -8.3+8.5y+9.3-14.54=8.2y-9.4 | | 4n-1/7=5 | | y=1/3* | | N=5+12 | | a+4b-2b-b= | | 63-45y=63 | | p=(2y+30) |